Innovation in Local Products as a Tourist Attraction in East Nusa Tenggara Province - Nugraha, Yudha Eka; Flora, Veronika A. S. M.; Plaituka, Christina Welly; Nasar, Asbi; Tana, Yunita (Jurnal Penelitian Pariwisata, 2023)
Tourism as one of the priority programs of the NTT government continues to strive to improve services and diversify tourism products, one of which is local-based products which are a tourism attraction for tourists who are looking for souvenirs as gifts when finished traveling. The application of innovation is a way that must be taken to keep the tourism business away from competition between tourism businesses, threats of unattractive products and failure to face tourism business obstacles. This research was conducted using a qualitative approach to the creative industries of Kupang City which are engaged in the business of native NTT products that are sold to tourism destinations as souvenirs. The results of this study indicate that the application of innovation that has been carried out is divided into 5 namely: product innovation, process innovation, managerial innovation, management innovation, and institutional innovation. Of the 2 innovation models, process innovation and product innovation are the innovations most often carried out to market locally based products. Keywords: Tourism Innovation, Tourism Products, Local Souvenirs, Creative Industries